Evaluation of Usability on Mobile Detector X-ray Absorption, Scattering, and Phased Image Phantom (Medico Legal Update, 2019)
Existing X-ray medical imaging acquired the image data of X-ray absorption difference using the differencein density of the subject tissue. X-ray scattering and phase contrast imaging technology is a technologythat dramatically increases boundary information between homogeneous materials of similar density usingscattering and phase contrast information. To acquire and evaluate absorption, scattering, and phase contrastimages, using the phantom made of polyethylene, on a round rod with a diameter of 3?1cm, a hole with adiameter of 0.5cm was drilled on 5 round rods, and the medical phantom was produced by sealing withsodium chloride, neon, calcium, phosphorus, and selenium powder. At a distance of 40cm from the focus,the distribution of absorbed doses have shown 1,277 ± 0.31?Gy in the center area. The measurement dosein the anode side direction was 110.1 ± 0.35?Gy and the cathode side direction was 117.7 ± 0.77?Gy. It hasshown dose inequality that depends on the geometry of the target. It has shown similar tendency in 60cm and80cm Compared with absorption images in graphite materials, it was confirmed that scattering and phasecontrast images were showing relatively high image information. These results are expected to be utilizedas an important basic data for reducing medical exposure dose and acquiring, evaluating and utilizing X-rayabsorption, scattering and phase contrast images.